Financial inclusion in Lebanon after the economic crisis - Mohamad Hijazi; Mohamad Saad; Sarah Sidani (Cogent Business & Management)
Lebanon has been experiencing a severe economic crisis in recent years, leading to a significant decline in access to financial services. A survey found that around 25% of individuals have closed their formal accounts, contributing to an increase in financial exclusion. This situation raises concerns about the crisis’s impact on financial inclusion. Therefore, this study aims to examine how the economic crisis has affected the level and determinants of financial inclusion in Lebanon. A quantitative approach was employed, using a causal research design with a sample of 1,050 Lebanese individuals from urban and rural areas. Logistic regression analysis was used to identify the demand-side factors influencing financial inclusion before and after the crisis. The findings indicate a one-third decrease in financial inclusion after the crisis. However, insurance and digital financial services remained relatively stable. Prior to the crisis, income was the primary factor influencing financial inclusion, but afterward, no specific demographic variable had a significant impact. The crisis has caused a loss of trust in Lebanon’s formal financial institutions and created a common economic challenge, overshadowing individual differences. The study suggests that policymakers should focus on restoring public trust in these institutions to address the decline in financial inclusion.